2023
DOI: 10.3390/su151511817
|View full text |Cite
|
Sign up to set email alerts
|

European Green Deal: The Impact of the Level of Renewable Energy Source and Gross Domestic Product per Capita on Energy Import Dependency

Valentyna Kukharets,
Taras Hutsol,
Savelii Kukharets
et al.

Abstract: The level of renewable energy use and economic development of a country, as separate indicators, have an influence on the level of energy resource imports, but the mutual impact of renewable energy sources and gross national product on the growth or decrease of energy imports dependency have not been studied. Therefore, the aim of this study was to evaluate the energy security of European countries by taking into account the consumption of renewable energy sources and the economic development of the countries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It set a goal of achieving climate neutrality by 2050, meaning that the European Union aims to balance its greenhouse gas emissions with removals, effectively eliminating its net contribution to climate change [35,36]. The Green Deal is closely tied to economic recovery efforts, especially in the wake of the COVID-19 pandemic [37][38][39].…”
Section: European Green Dealmentioning
confidence: 99%
See 1 more Smart Citation
“…It set a goal of achieving climate neutrality by 2050, meaning that the European Union aims to balance its greenhouse gas emissions with removals, effectively eliminating its net contribution to climate change [35,36]. The Green Deal is closely tied to economic recovery efforts, especially in the wake of the COVID-19 pandemic [37][38][39].…”
Section: European Green Dealmentioning
confidence: 99%
“…Bulgaria anticipates substantial private sector investment of around EUR 2.4 billion, while Lithuania plans for EUR 815 per capita in private investments. This collaboration aims to leverage additional capital for sustainable initiatives [39,40].…”
Section: European Green Dealmentioning
confidence: 99%
“…They concluded that several determinants had a positive impact on economic growth driven by the large consumption of fossil energy, and thus an increase in growth at the expense of an increase in CO2 emissions, which negatively affected environmental safety. Kukharets et al (2023) studied the issue of energy security in the European Union, by examining the impact of the level of renewable energy, as well as the level of development, on the degrees of dependence on energy imports, within the framework of the European Green Deal. It was done using regression analysis of data covering the period 2011-2021.…”
Section: Economics and Businessmentioning
confidence: 99%
“…This is stated in the European Union Deal. According to the European Green Deal, it is necessary to reduce greenhouse gas emissions by 55% (from 1990 to 2023) and ensure sustainable economic growth without increasing the use of fossil fuel resources [3]. Reducing greenhouse gas emissions requires an increase in the Energies 2023, 16, 7490 2 of 15 share of renewable sources in energy production [4] and the development of new types of relevant equipment [5].…”
Section: Introductionmentioning
confidence: 99%